DETERMINANTS OF COMPANY STOCK SPLIT DECISIONS (STUDY ON GO PUBLIC COMPANIES LISTED ON THE BEI) - Mahendra Ryansa Gallen Gagah Pratama; Nadia Rachma Puspita; Yeni Nur Prilanita (Jurnal Ilmiah WUNY, 2023)
This study aims to determine the effect of the high level of stock prices, company financial performance, and stock trading liquidity on stock split decisions in companies listed on the Indonesia Stock Exchange. It uses a quantitative approach. The research population includes all companies listed on the Indonesia Stock Exchange in the 2014-2016 period. The sample was determined by purposive sampling technique and 40 companies were obtained. The analytical method used in this study is logistic regression analysis.Based on research results, it can be concluded that the level of overpriced stock prices by proxy Price Earning Ratio (PER) has a significant positive effect on the company's stock split decision. The level of expensive stock prices proxied by Price Book Value (PBV) has a significant positive effect on the company's stock split decision. The company's financial performance by proxy Earnings Per Share (EPS) has a significant positive influence on the company's stock split decision. The company's financial performance proxied by Return on Assets (ROA) has a significant negative effect on the company's stock split decision. Stock trading liquidity proxied by Trading Volume Activity (TVA) has a significant negative effect on the company's stock split decision. The Nagelkerke R Square value in this study is 0. 702 which means the ability of the variable level of expensive stock prices, the company's financial performance, and stock trading liquidity explains the company's decision variable to do a stock split of 70.2%. The remaining 29.8% of the dependent variable is explained by other factors outside the model.